2024
DOI: 10.3897/natureconservation.55.114385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of management complexity on the composition, plant functional dominance relationships and physiognomy of high nature value grasslands

Róbert Kun,
Dániel Babai,
András István Csathó
et al.

Abstract: A significant proportion of Europe’s species-rich grasslands are semi-natural habitats. They have a long history of traditional management. Several studies have been carried out to conserve them, resulting in the establishment of subsidised conservation management schemes. On the other hand, many of these conservation management schemes have failed to provide locally adaptive solutions to maintain the diversity and functional status of species-rich grasslands. In addition, few studies have compared the conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…This also explains the similarity in species composition (Figures 3 and 4) and the distribution of the endemic species with conservation interest among the different clusters. Indeed, the highest number of species with conservation interest held by clusters 1 and 2 (Table 4) is in accord with findings made by several authors, namely that when grazing is conducted in a non-intensive manner, it tends to promote greater biodiversity, and the effects of such practices can persist for an extended period of time [87][88][89][90][91][92].…”
Section: Discussionsupporting
confidence: 89%
“…This also explains the similarity in species composition (Figures 3 and 4) and the distribution of the endemic species with conservation interest among the different clusters. Indeed, the highest number of species with conservation interest held by clusters 1 and 2 (Table 4) is in accord with findings made by several authors, namely that when grazing is conducted in a non-intensive manner, it tends to promote greater biodiversity, and the effects of such practices can persist for an extended period of time [87][88][89][90][91][92].…”
Section: Discussionsupporting
confidence: 89%
“…The lack of colonisation of the grass cover by invasive and quarantine species in the experimental areas of the cherry orchard can be explained by moderate mowing (4 times during the growing season). Control over invasive species is considered active recovery (Grašič et al, 2023), and moderate mowing (or moderate grazing) as reported (Yang et al, 2022;Kun et al, 2024) accelerate recovery processes in the phytocoenoses of meadows and pastures (the so-called "moderate concern hypothesis"). In a global ecological sense, ruderants provide invaluable ecosystem services, namely, a dense cover of natural grasses mitigates the effects of climate warming, binds carbon and thereby reduces CO 2 emissions in the atmosphere (Berlinches de Gea et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of colonisation of the grass cover by invasive and quarantine species in the experimental areas of the cherry orchard can be explained by moderate mowing (4 times during the growing season). Control over invasive species is considered active recovery (Grašič et al, 2023), and moderate mowing (or moderate grazing) as reported Kun et al, 2024) accelerate recovery processes in the phytocoenoses of meadows and pastures (the so-called "moderate concern hypothesis"). In a global ecological sense, ruderants provide invaluable ecosystem services, namely, a dense cover of natural grasses mitigates the effects of climate warming, binds carbon and thereby reduces CO 2 emissions in the atmosphere (Berlinches de Gea et al, 2023).…”
Section: Discussionmentioning
confidence: 99%